Anxious suitcases and their contents: Experiences of the war in Ukraine through a material lens. (28th January 2023) - Sopova, Alisa
Abstract: The war in Ukraine has uprooted millions of people, forcing them to confront their habitual material environment of home and everyday life in new and unexpected ways. This is particularly the case when they evacuate and must decide what to take with them and what to leave behind. This photo‐essay comprises a selection of objects that, at the moment of crisis, have stepped in to embody important aspects of their owners' lives. As their owners reflect on them, these objects raise important questions about the affective qualities of materiality. They suggest how in wartime, large‐scale loss and destruction lay bare otherwise taken‐for‐granted affective entanglements between the human and the nonhuman.